2021
DOI: 10.1371/journal.pone.0252550
|View full text |Cite
|
Sign up to set email alerts
|

Early expressions of psychopathology and risk associated with trans-diagnostic transition to mood and psychotic disorders in adolescents and young adults

Abstract: Objectives The heterogeneity and comorbidity of major mental disorders presenting in adolescents and young adults has fostered calls for trans-diagnostic research. This study examines early expressions of psychopathology and risk and trans-diagnostic caseness in a community cohort of twins and non-twin siblings. Methods Using data from the Brisbane Longitudinal Twin Study, we estimated median number of self-rated psychiatric symptoms, prevalence of subthreshold syndromes, family history of mood and/or psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 42 publications
(111 reference statements)
1
13
0
Order By: Relevance
“…Given the advantages of self-report instruments (eg, quick to administer, easy to score and the suitability for being used as part of a broad survey),48 we focused on these measures. This fits with the current recognised need to improve the early detection of mental health difficulties by addressing a broad range of symptoms and underlying transdiagnostic mechanisms 49 50…”
Section: Introductionsupporting
confidence: 66%
“…Given the advantages of self-report instruments (eg, quick to administer, easy to score and the suitability for being used as part of a broad survey),48 we focused on these measures. This fits with the current recognised need to improve the early detection of mental health difficulties by addressing a broad range of symptoms and underlying transdiagnostic mechanisms 49 50…”
Section: Introductionsupporting
confidence: 66%
“…The 12-item Somatic and Psychological Health Report (SPHERE-12) measured the presence/absence of somatic (SOMA-6 subscale, e.g., hypersomnia, anergia) and anxious-depressive symptoms (PSYCH-6 subscale, e.g., feeling overwhelmed, hopelessness) over recent weeks [27]. Five hypo-manic symptoms (persistence >2 days of, e.g., decreased need for sleep, feeling elated) were examined using an investigator-devised self-rating scale (used in several of our studies) [23, 24, 28]. Six psychotic-like symptoms (e.g., auditory hallucinations) were assessed using a tool adapted in part from the Community Assessment of Psychic Experiences [29].…”
Section: Methodsmentioning
confidence: 99%
“…The current study uses DBNs to examine the temporal relationships among self-rated psychological symptoms and associated social, occupational, and lifestyle factors across two waves of follow-up (~5–6-year interval) of a cohort of young people recruited to the Brisbane Longitudinal Twin Study (BLTS), a prospective, community-based study of adult twins and nontwin siblings. In a series of recent studies, we examined the progression of subthreshold syndromes (i.e., depression-like, hypo-manic-like, and psychotic-like) to full-threshold mood and psychotic disorders [23, 24]. Here, we focus on cohort members without evidence of a full-threshold disorder, and we model two DBNs to examine two questions: (a) what are the relationships among self-rated psychological symptoms, impairment, alcohol and other substance use, and perceived social support across the “Nineteen and Up” (19Up) and “Twenty Five and Up” (25Up) study waves; and (b) what are the relationships among these factors at 19Up and subsequent progression to a depression-like, hypo-manic-like, and/or psychotic-like subthreshold syndrome at 25Up?…”
Section: Introductionmentioning
confidence: 99%
“…Taking a more transdiagnostic perspective of psychopathology ( 25 , 26 ), one way to approach this is to analyze PEs in conjunction with other symptoms and vulnerability factors in clinical and non-clinical populations within the framework of the extended psychosis phenotype model ( 27 ). One technique that allows for this is latent profile analysis (LPA), a categorical latent variable modeling approach ( 28 , 29 ) allowing for classifications of individuals into latent subgroups based on their scoring patterns on a range of manifest variables.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, it has been shown that adolescents endorsing PEs use more emotional suppression and less cognitive reappraisal ( 45 ), which is in turn associated with higher comorbid symptomatology ( 46 ). However, the evidence of emotional difficulties in psychotic disorders remains mixed ( 25 , 47 ).…”
Section: Introductionmentioning
confidence: 99%